2019
DOI: 10.1200/jco.19.00858
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of T-DM1 Plus Neratinib in Patients With Metastatic HER2-Positive Breast Cancer: NSABP Foundation Trial FB-10

Abstract: PURPOSE Patients with human epidermal growth factor receptor 2 (HER2)–positive metastatic breast cancer eventually develop resistance to dual-antibody therapy with trastuzumab plus pertuzumab. Mechanisms of resistance have not been well elucidated. We evaluated the safety, tolerability, and efficacy of ado-trastuzumab emtansine (T-DM1) plus neratinib in patients who progressed on trastuzumab plus pertuzumab. PATIENTS AND METHODS In this 3 + 3 dose-escalation study, patients with metastatic breast cancer who pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 35 publications
2
43
0
Order By: Relevance
“…3G) and continued with this treatment until intracranial progression at week 18 (at that time the patient remained in confirmed partial response extracranially). This prompt response is consistent with our preclinical data that cotreatment with neratinib improved internalization and efficacy of T-DM1, and with a recently published trial showing encouraging efficacy and tolerability of T-DM1 and neratinib in metastatic breast cancer, albeit in a T-DM1-naïve setting (27).…”
Section: Irreversible Her Kinase Inhibitors Enhance Her2 Internalizatsupporting
confidence: 91%
See 1 more Smart Citation
“…3G) and continued with this treatment until intracranial progression at week 18 (at that time the patient remained in confirmed partial response extracranially). This prompt response is consistent with our preclinical data that cotreatment with neratinib improved internalization and efficacy of T-DM1, and with a recently published trial showing encouraging efficacy and tolerability of T-DM1 and neratinib in metastatic breast cancer, albeit in a T-DM1-naïve setting (27).…”
Section: Irreversible Her Kinase Inhibitors Enhance Her2 Internalizatsupporting
confidence: 91%
“…Although combined neratinib and T-DM1 elicited an ORR of 63% with a manageable toxicity profile in a phase I trial of 19 patients with HER2-positive breast cancer previously treated with trastuzumab-and pertuzumab-based therapies (27), these responses were not compared to T-DM1 monotherapy and no data are available on the efficacy of this combination in patients with T-DM1-refractory breast cancer. Furthermore, there are no current clinical trials evaluating the clinical benefit of the combination of T-DM1 and pan-HER irreversible inhibitors in comparison with T-DM1 monotherapy in ERBB2-mutant or -amplified lung cancers.…”
Section: Discussionmentioning
confidence: 99%
“…No DLTs were observed at the RP2D. 11 A third multicenter, international, randomized phase 2 trial, NEFERT-T (Study Evaluating Neratinib Plus Paclitaxel vs Trastuzumab Plus Paclitaxel in ErB-2 Positive Breast Cancer; ClinicalTrials.gov identifier NCT00915018), compared trastuzumab plus paclitaxel versus neratinib plus paclitaxel as first-line therapy in 479 patients with previously untreated, HER2-positive MBC. All patients received weekly paclitaxel (80 mg/m 2 ) on days 1, 8, and 15 of at 21-day cycle with either daily neratinib (240 mg) or weekly trastuzumab.…”
Section: Neratinibmentioning
confidence: 99%
“…Recent clinical studies with small molecule inhibitors, including tyrosine kinase inhibitors, anti-ERBB2 agents, PI3K/Akt/mTOR inhibitors, and CDK4/6 inhibitors, have shown promise in inhibiting proliferation and metastasis in ERBB2 + BC [ 10 , 11 , 12 ]. For instance, inhibitors targeting ERBB1 and c-MET receptors that are upregulated during BC metastasis, are currently being investigated in clinical trials for patients with existing metastasis [ 13 , 14 , 15 , 16 ]. Neratinib (NER), an irreversible pan-ERBB family inhibitor, has been reported to be efficacious in metastatic BC patients in combination with capecitabine [ 17 ] and paclitaxel [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Neratinib (NER), an irreversible pan-ERBB family inhibitor, has been reported to be efficacious in metastatic BC patients in combination with capecitabine [ 17 ] and paclitaxel [ 18 , 19 ]. Further, the data from two different clinical trials showed that NER, in combination with either capecitabine or T-DM1, was effective against brain metastatic ERBB2 + BC, with grade 3 and 4 levels of toxicity, respectively [ 14 , 15 ]. A recent study in the ERBB2 + spontaneous metastasis model showed that NER monotherapy (60 mg/kg) inhibited proliferation and distant metastasis in BALB/c mice via inhibition of ferroptosis [ 20 ].…”
Section: Introductionmentioning
confidence: 99%